An investigation of the association between structural proteins and lipids with scalp hair curvature - Mukonyora, Michelle (Department of Medicine, 2026)
Scalp hair is increasingly being used as a non-invasive analytical sample in diagnostic and forensic medicine. However, variable sensitivities for detection of hair biomarkers were observed, whereby African hair generally incorporated higher drug levels than Asian and Caucasian hair types. It was hypothesized that higher absolute lipid amounts in African curly hair may affect the rate at which lipid-soluble metabolites are passively incorporated into the growing hair shaft. Furthermore, the interactions between structural proteins and lipids in scalp hair may be associated with hair curvature, though the exact mechanism is unknown. This study is the first to investigate the hair proteome and lipidome in the same group of hair samples using a multiomics approach to determine how they both relate to each other, and to hair curvature. After ethical approval, hair of varying curvature was collected from 90 participants and classified from straight to curly objectively (type I – VI) using a validated tool. Hair proteins were extracted and analysed using an ultra-high performance liquid chromatography quadrupole time of flight (UPLC-QToF) mass spectrometer and the data analysed using various bioinformatics tools and gene ontology analyses. Hair lipids were extracted and analysed using a gas chromatography-triple quadrupole (GC-QqQ) mass spectrometer, various bioinformatics tools, and lipid pathway enrichment analyses. The combined proteomics and lipidomics quantification data were analysed using both supervised and unsupervised classification methods to build hair proteolipidomic models. We identified a total of 420 hair proteins, which is comparable to the highest numbers in published hair studies. We also identified the largest number of chaperones compared to any published hair study, where nine out 15 are described for the first time in hair. Importantly, seven proteins, belonging to four protein groups (transketolase, iron-sulfur cluster scaffold homolog, proline-rich protein 29, heat shock protein family A) were differentially expressed (p-value < 0.05) and described in hair for the first time. Proline-rich protein 29 was the only differentially expressed protein with a linear increase from hair type I to VI. This is also the first study to report differentially expressed proteins between all six geometric hair types. The differentially expressed hair proteins regulate various aspects of energy metabolism, and they are involved in processes known to drive keratinocyte differentiation and maintain homeostasis in the hair follicle and skin. A total of 77,060 lipid features (RT and m/z) were found, and 3,084 were identified at the lipid species level (RT, m/z, and lipid subclass), which is the largest number of hair lipids identified in any published hair study to date. For the first time, 129 differentially expressed hair lipids (p-value < 0.01) in hair of different curvature were identified. A subset of 19 differentially expressed hair lipids belonging to nine lipid subclasses (sterol lipids, steroids, hydrocarbons, fatty acids, fatty acyl carnitines, ceramides, endocannabinoids, wax esters, and ethyl esters) were characterised and pre-validated using multiple reaction monitoring (MRM) in separate hold-out hair samples. These lipids regulate necroptosis, as well as sphingolipid signalling and metabolism (FDR < 0.05). We built hair proteolipidomic models for the first time, which revealed that the hair proteolipidome comprises several heterogeneous subclusters. Also, that proteins showed a poor correlation with hair curvature as confirmed by poor/moderate ROC scores (0.6 to 0.8), whereas lipids correlated well with hair curvature as confirmed by excellent ROC scores (0.96 to 1). The hair proteolipidome further revealed protein folding, formation of the extracellular matrix, and the Wnt/β-catenin signalling pathway as being associated with hair curvature (FDR < 0.05). In conclusion, our investigation of baseline lipid and protein profiles across various geometric hair types confirms previous data of low correlation between proteins and hair curvature. However, this study identified, for the first time, 9 novel chaperones in hair. Proline-rich protein 29, also novel, was the only protein which increased from hair type I to VI. This study also reports the largest number of lipids in any hair study, is the first to report lipid sub-classes and multi-omics which confirmed the high correlation between lipids and hair curvature. A limitation of this study is that a more robust computational quantification method for hair curvature variations was not used because it was published after this study commenced. Future studies are needed to elucidate the potential contribution of identified molecules to hair curvature variation.